2020
DOI: 10.1002/ccd.29276
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural anemia in females undergoing transcatheter aortic valve implantation: Insights from the WIN‐TAVI registry

Abstract: Objectives To assess the impact of anemia on clinical outcomes in female patients enrolled in the Women's InterNational transcatheter aortic valve implantation (WIN‐TAVI) registry. Background Anemia is highly prevalent among females who constitute half of TAVI candidates, yet, its clinical significance remains poorly investigated. Methods Patients were divided into three groups according to preprocedural hemoglobin (Hb) level: (1) no anemia (Hb ≥12 g/dl), (2) mild‐to‐moderate anemia (10 ≤ Hb <12 g/dl), and (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
(37 reference statements)
1
15
0
1
Order By: Relevance
“…About one-fourth of female patients in our analysis presented a severe impairment of renal function that is frequently related to lower levels of hemoglobin. According to recent data, severe anemia in women undergoing TAVR has been associated with increased rates of VARC-2 efficacy endpoint, including stroke [ 37 ]. Although it is well known that TAVR reduces the risk of bleeding compared with SAVR [ 38 ], a higher incidence of anemia may partially explain the higher rate of major bleeding, also in the long term, affecting women undergoing TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…About one-fourth of female patients in our analysis presented a severe impairment of renal function that is frequently related to lower levels of hemoglobin. According to recent data, severe anemia in women undergoing TAVR has been associated with increased rates of VARC-2 efficacy endpoint, including stroke [ 37 ]. Although it is well known that TAVR reduces the risk of bleeding compared with SAVR [ 38 ], a higher incidence of anemia may partially explain the higher rate of major bleeding, also in the long term, affecting women undergoing TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…The WIN-TAVI registry has been previously described. [13][14][15][16] Briefly, this prospective registry included women undergoing TAVR with a commercially available device for symptomatic aortic stenosis in 19 high-volume centers in Europe and the United States between January 2013 and December 2015. All patients were deemed suitable for TAVR by the local heart team and provided informed consent to their data's anonymous processing.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-existing right bundle branch block (RBBB) was associated with a high risk of post-TAVR PPI (OR 3.62, 95% CI 1.85-7.06, p < 0.001), while implantation of balloon-expandable prosthesis was associated with a lower risk (OR 0.47, 95% CI 0.30-0.74, p < 0.001). Post-TAVR PPI prolonged in-hospital stay by a median of 2 days (11 [9][10][11][12][13][14][15][16] days in PPI vs. 9 [7][8][9][10][11][12][13][14] days in no-PPI, p = 0.005), yet risks of VARC-2 efficacy and safety endpoints at 1 year were similar in both groups ( adj HR 0.95, 95% CI 0.60-1.52, p = 0.84 and adj HR 1.22, 95% CI 0.83-1.79, p = 0.31, respectively).…”
mentioning
confidence: 99%
“…The prevalence of anemia in our study population was 54%, which is consistent with prior reports. 8,19,20 Multiple studies have shown worse outcomes during long-term follow-up in anemic patients undergoing TAVR compared to those without pre-existing anemia. 8,10,11 However, these findings could be driven by the fact that elderly anemic patients have worse outcomes independent of cardiac interventions.…”
mentioning
confidence: 99%
“…8,19,20 Multiple studies have shown worse outcomes during long-term follow-up in anemic patients undergoing TAVR compared to those without pre-existing anemia. 8,10,11 However, these findings could be driven by the fact that elderly anemic patients have worse outcomes independent of cardiac interventions. 21,22 Conversely, other studies have failed to demonstrate an increased risk of periprocedural and 30-day mortality after TAVR in those subsets of patients with anemia indicating that TAVR can be safely performed in these otherwise higher risk patients.…”
mentioning
confidence: 99%